AngioJet thrombectomy with extracorporeal membrane oxygenation support for an acute large-scale pulmonary embolism with bilateral atrial thrombosis: a case report of catastrophic antiphospholipid syndrome - Ji, Jianyu; Jiang, Lei; Wang, Wei; Chi, Xinyu; Dong, Jinda; Lu, Liqiu; Huang, Minyan; Wei, Xiutian; Pang, Guangbao; Pang, Jing; Xiong, Bin; Xiang, Shulin (Frontiers in Cardiovascular Medicine, 2024)
Background Catastrophic Antiphospholipid Syndrome (CAPS), a severe systemic autoimmune disorder, predominantly causes life-threatening multi-organ failure, with a high mortality rate. It primarily affects small vessels, seldom impacting large vessels. Notably, acute massive pulmonary embolism (PE) with bilateral atrial thrombosis is an exceptional occurrence in CAPS. Acute pulmonary embolism (PE) is a common cardiovascular disease that progresses rapidly and has a high mortality rate. Acute massive PE combined with bilateral atrial thrombosis has an even higher mortality rate. PE treatments primarily include pharmaceuticals, catheter interventions, and surgical measures, with integrated treatment strategies demonstrating promising outcomes in clinical practice. Extracorporeal membrane oxygenation (ECMO) can provide cardiopulmonary support for the treatment of high-risk PE patients and is a proven therapeutic measure. Methods This report presents the case of a 52-year-old male admitted due to fever and sudden onset of impaired consciousness, with cardiac ultrasound and pulmonary artery CT angiography revealing an acute large-scale pulmonary embolism accompanied by bilateral atrial thrombosis, with the condition rapidly worsening and manifesting severe respiratory and circulatory failure. With ECMO support, the patient underwent a thrombectomy using an AngioJet intervention. The diagnosis of CAPS was confirmed through clinical presentation and laboratory examination, and treatment was adjusted accordingly. Results The patient made a successful recovery and was subsequently discharged from the hospital. Conclusion In CAPS patients, the rare instance of acute massive PE accompanied by bilateral atrial thrombosis significantly risks severe respiratory and circulatory failure, adversely affecting prognosis. Early initiation of ECMO therapy is crucial, offering a vital opportunity to address the root cause. In this case report the patient was successfully treated with an AngioJet thrombectomy supported by ECMO.